Elastisitas Transmisi Harga dan Efisiensi Pemasaran Ikan Nila di Kabupaten Indramayu - Nur Alia Sari; Teguh Iman Santoso; Supriyadi Supriyadi; Karto Karto (Universitas Wiralodra, 2026)
This study examines the marketing efficiency of tilapia (Oreochromis niloticus) in Indramayu Regency by analyzing price transmission elasticity between producer and consumer levels. Secondary data were obtained from the Central Bureau of Statistics (BPS) and the Department of Fisheries and Marine Affairs of Indramayu for the period 2020–2024. A log-linear regression model was employed to estimate the elasticity coefficient as an indicator of market integration efficiency. The findings reveal an elasticity value of 0.752, indicating that a 1% increase in consumer prices leads to only a 0.752% increase in producer prices. This result suggests that price transmission remains imperfect and that the marketing system for tilapia in Indramayu is not yet efficient. The inefficiency is largely attributed to an extended distribution chain, the dominance of intermediaries, and limited price information access among fish farmers. Strengthening cooperative institutions and implementing digital market information systems are recommended to enhance marketing efficiency and improve farmers’ welfare. This study contributes to the literature on aquaculture marketing efficiency in Indonesia by emphasizing the significance of institutional structures and digitalization in promoting fair and transparent price transmission.